IMPLEMENTASI PILAR PENDIDIKAN SEKOLAH DAN MADRASAH PADA ERA REVOLUSI INDUSTRI 4.0 - Saidah; Nur Hikmah (At- Ta'lim : Jurnal Pendidikan, 2024)
Advances in science and technology are very rapid, reaching the fourth industrial revolution (4.0). Science and technological advances have an impact on education, both positively and negatively. It is vital to have pillars in the educational process. Learning to know, learning to do, learning to live together, learning to be, and learning to believe in God are the pillars of education. The pillars are used during the learning process.